Cardiac Repair With Echocardiography-Guided Multiple Percutaneous Left Ventricular Intramyocardial Injection of hiPSC-CMs After Myocardial Infarction - Wu, Xun; Wang, Di; Qin, Kele; Iroegbu, Chukwuemeka Daniel; Xiang, Kun; Zhou, Yuanjing; Guan, Qing; Tang, Weijie; Peng, Jun; Guo, Jianjun; Yang, Jinfu; Fan, Chengming (Frontiers in Cardiovascular Medicine, 2021)
Objective: We investigated the potency of cardiac repair based on echocardiography-guided multiple percutaneous left ventricular intramyocardial injection of human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) after myocardial infarction (MI). Methods: Mice with surgically induced MI were randomly divided into three groups (n = 8 in each group) and subjected to echocardiography-guided percutaneous left ventricular infarcted border injection of hiPSC-CMs (single dose; 10 μl 3 × 105 cells) or repeated injections of hiPSC-CMs at post-MI weeks 1 and 2 (multiple doses). The sham group of animals underwent all surgical procedures necessary for MI induction except for ligation. Then 4 weeks after MI, heart function was measured with transthoracic echocardiography. Engraftment was evaluated through the detection of human-specific cardiac troponin T. Infarct size and collagen volume were calculated with Sirius Red/Fast Green staining. Angiogenesis was evaluated with isolectin B4 staining. Cardiac remodeling was evaluated from the cardiomyocyte minimal fiber diameter in the infarcted border zone. Apoptosis was detected via TdT-mediated dUTP Nick-End Labeling (TUNEL) staining in cardiomyocytes from the infarcted border zone. Results: No mice died after echocardiography-guided percutaneous left ventricular intramyocardial injection. hiPSC-CMs were about nine-fold higher in the multiple-dose group at week 4 compared to the single-dose group. Multiple-dose transplantation was associated with significant improvement in left ventricular function, infarct size, angiogenesis, cardiac remodeling, and cardiomyocyte apoptosis. Conclusion: Echocardiography-guided multiple percutaneous left ventricular intramyocardial injection is a feasible, satisfactory, repeatable, relatively less invasive, and effective method of delivering cell therapy. The delivery of hiPSC-CMs indicates a novel therapy for MI.